A nineteen weeks cervical ectopic pregnancy case - Atilgan, Remzi; Şimşek, Mehmet; Özkan, Zehra Sema; Göktolga Pinar, Gülser; Orak, U?ur; Kumbak Aygün, Banu; Kandemir Deniz, Yaprak (My University, 2013)
Cervical ectopic pregnancy is a rare ectopic pregnancy type that settles in endocervical canal and it threatens human life. It is seen 1/1000-18.000 alive pregnancies. Its occurence mechanism is unknown but the damage of endocervical canal and endometrial layer may play role at ethiology. Bleeding volume, gestational week, settled area of gestasional sac, depth of trophoblastic invasion and ?-HCG level are important for the management of cervical ectopic pregnancy. Conservative and radical managements are selected for threatment. Radical management is hysterectomy and it is used if bleeding is very heavy and threatens human life. We prefer a 36-years-old woman haves a nineteen weeks cervical ectopic pregnancy gones with massive hemorrhage and done hysterectomy. Copyright © 2013 by Türkiye Klinikleri.
On dokuz haftalik bir servikal ektopik gebelik olgusu
Keywords: Hysterectomy; Pregnancy, ectopic